A RISKS OF CORRUPTION DURING COVID-19 - Slamkov, Gjorgi (International Scientific Journal Vision, 2021)
The paper addresses the issue of risks of corruption during dealing with the pandemic that marked 2020, ie COVID -19. Namely, the crisis caught almost all countries and imposed the need for urgent measures to reduce the harmful consequences. However, the shortening of deadlines or simplification of procedures has created conditions for the occurrence of corrupt activities, ie, misuse of state resources for private purposes. In the paper, the most risky points for corruption during the COVID-19 crisis are public procurement, economic assistance from the state to citizens and companies, as well as the decline of integrity. The paper lists several scandals of a corrupt nature during the pandemic that arise from the above-mentioned risk points, which include procurement at extremely high prices, low quality of goods, secrecy of the procedure, missing humanitarian aid, abuse of quarantine. The paper emphasizes that the most effective tool for fighting corruption is transparency, and in terms of COVID -19 and the challenges it brings, transparency should be at a higher level. Accountability, informing the citizens, access to public information are tools aimed at reducing the risks of corruption, strengthening trust in the system and the rule of law.